Analysis of peripheral blood variables in evaluation and prediction of adverse outcomes with hypertensive disorders of pregnancy - Yingdi Jiang; Lu Dai; Jiang Lin; Yanjie Zhou (BMC Pregnancy and Childbirth)
Abstract Background Hypertensive disorders of pregnancy (HDP) constitute a major obstetric complication globally, contributing significantly to perinatal morbidity and mortality, as well as to the incidence of severe pregnancy-related adverse outcomes. This study aims to evaluate the selected biomarkers and other parameters in the diagnosis and prediction of adverse pregnancy outcomes in women with HDP. Methods We enrolled a total of 165 pregnant women with HDP and 41 healthy pregnant women. Patients with HDP were subcategorized into gestational hypertension (GH), preeclampsia (PE), and severe preeclampsia (sPE). Using univariate analysis, we identified selected biomarkers and routine prenatal clinical indicators and further evaluated their associations with adverse pregnancy outcomes. Finally, a predictive nomogram was then developed using multivariable logistic regression. The predictive performance of the model was comprehensively evaluated through receiver operating characteristic (ROC) curves, calibration curves, decision curve analysis, and clinical impact curves. Results Levels of N-terminal pro-brain natriuretic peptide (NT-proBNP), lactate dehydrogenase (LDH), and platelet distribution width (PDW) showed a positive correlation with HDP severity. Notably, concentrations of these three peripheral blood variables were significantly higher in patients who experienced adverse pregnancy outcomes compared to those HDP patients without complications (P < 0.01). Multivariate logistic regression analyses further confirmed that gestational age (GA), NT-proBNP, LDH, and PDW are independent risk factors for adverse pregnancy outcomes in HDP patients (P < 0.01). The ROC curves demonstrated that combining GA with NT-proBNP, LDH, and PDW provided stronger predictive value for adverse outcomes. Furthermore, the nomogram's calibration curve indicated excellent model calibration. The decision curve analysis (DCA) showed that the nomogram is of practical significance. Conclusions Serum NT-proBNP, LDH, and PDW expressions are strongly associated with HDP severity, and these peripheral blood variables, along with gestational age (GA), are independent risk factors for predicting adverse outcomes in pregnant women with HDP. Moreover, constructed a nomogram that can easily predict and evaluate the risk of adverse pregnancy outcomes in women with HDP.